2012
DOI: 10.1007/s12015-012-9398-z
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Programming and Risk: The Birthplace of Cardiovascular Disease?

Abstract: Epigenetics, through control of gene expression circuitries, plays important roles in various physiological processes such as stem cell differentiation and self renewal. This occurs during embryonic development, in different tissues, and in response to environmental stimuli. The language of epigenetic program is based on specific covalent modifications of DNA and chromatin. Thus, in addition to the individual identity, encoded by sequence of the four bases of the DNA, there is a cell type identity characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 172 publications
(177 reference statements)
0
23
0
Order By: Relevance
“…22 The importance of DNA methylation has been shown, for example, for the (dys)regulation of inducible nitric oxide synthase, whereas specific histone modifications have been identified that are involved in the fixation of proinflammatory gene expression patterns in diabetic disease models. 31 Platelet function also seems to be crucially dependent on physiological epigenetic imprinting. 32 All these processes are among the mechanisms considered important in smokingassociated cardiovascular pathology.…”
Section: Epigenetics Of Tobacco-associated Cardiovascular Diseasementioning
confidence: 99%
“…22 The importance of DNA methylation has been shown, for example, for the (dys)regulation of inducible nitric oxide synthase, whereas specific histone modifications have been identified that are involved in the fixation of proinflammatory gene expression patterns in diabetic disease models. 31 Platelet function also seems to be crucially dependent on physiological epigenetic imprinting. 32 All these processes are among the mechanisms considered important in smokingassociated cardiovascular pathology.…”
Section: Epigenetics Of Tobacco-associated Cardiovascular Diseasementioning
confidence: 99%
“…The responses of cells to mechanical cues have emerged as a general component of the chronic evolution of cardiovascular diseases and aging [22], a process with an important epigenetic component [23]. Taken together, these data suggest a tight relationship between the mechanosensitivity of CFs and downstream profibrotic cell signaling.…”
Section: Introduction: Relevance Of Cell Mechanics In Cardiac Fibrosismentioning
confidence: 89%
“…In particular, cells cultured in contact with high stiffness substrates appear the gene expression setting acquired in the stiff environment, even after shifting into a soft environment. Thus, similar to the so-called epigenetic memory associated with the exposure of cells to altered metabolic conditions (e.g., hyperglycemia) [47], tissue mechanics could also irreversibly affect the expression of pathology-related genes, even after reversion of matrix mechanics to normal conditions. In keeping with this hypothesis, there is the finding that migratory epithelial cells primed on hard ECM for a defined duration migrate faster and display higher actomyosin expression compared to controls even when in contact with a softer matrix [48].…”
Section: Role Of Mechanical Factors In Myofibroblast Activation and Cmentioning
confidence: 99%